Theoretical-doctrinal guidelines for the interpretation of the concursus of crimes in Ecuadorian criminal law - Muñoa Vidal, Tania (2024)
The objective of this theoretical reflection article is to substantiate the essential theoretical assumptions that must serve as a basis for the conception and application of bankruptcy matters in the Criminal Law of the Ecuadorian model from the perspective of the current Comprehensive Organic Criminal Code, in order to contribute to its improvement. The research was designed with a qualitative approach, and through a bibliographic review process supported by analysis, synthesis, inductive-deductive, and exegetical methods, it allowed theoretical reflection on the topic. The results validated what was stated by the authors about the problems raised in the application of bankruptcy competition and the types of criminal competitions. Which allowed us to conclude the need to specify, from theory, the nature of the different categories and their conceived penological effects, in order to correctly apply the legal institutions that make up the bankruptcy matter.